Progress Toward the Health MDGs : Are the Poor Being Left Behind? - Wagstaff, Adam; Bredenkamp, Caryn; Buisman, Leander R. (World Bank, Washington, DC, 2014)
This paper looks at differential progress on the health Millennium Development Goals between the poor and better-off within countries. The findings are based on original analysis of 235 Demographic and Health Surveys and Multiple Indicator Cluster Surveys, spanning 64 developing countries over the period 1990-2011. Five health status indicators and seven intervention indicators are tracked for all the health Millennium Development Goals. In most countries, the poorest 40 percent have made faster progress than the richest 60 percent. On average, relative inequality in the Millennium Development Goal indicators has been falling. However, the opposite is true in a sizable minority of countries, especially on child health status indicators (40-50 percent in the cases of child malnutrition and mortality), and on some intervention indicators (almost 40 percent in the case of immunizations). Absolute inequality has been rising in a larger fraction of countries and in around one-quarter of countries, the poorest 40 percent have been slipping backward in absolute terms. Despite reductions in most countries, relative inequalities in the Millennium Development Goal health indicators are still appreciable, with the poor facing higher risks of malnutrition and death in childhood and lower odds of receiving key health interventions.